Pelatiahan Gerak Dasar Bola Voli Di SMP PGRI 06 Gandrungmangu Desa Karanggintung Tahun 2023 - Kusmiyati Kusmiyati; Dian Imam Saefulah; Roja Mustaqim (Compromise Journal Community Proffesional Service Journal, 2023)
Training on basic volleyball movements was held with the hope of increasing students' awareness of the importance of basic movements in the game of volleyball. Apart from that, basic volleyball movements are a series of movements used by volleyball players to control and manipulate the ball. These basic movements include receiving and attacking movements. By mastering the basic movements of volleyball, students can develop skills and abilities in playing volleyball. The basic movements of volleyball will go through several stages to get to the final stage, namely (1) providing material starting from the meaning, history of volleyball and when volleyball came to Indonesia. (2) practice basic volleyball movements (top serve, bottom serve, top pass and bottom pass). (3) there are volleyball games in general where children will play volleyball and in the game there are basic volleyball movements (bottom serve, top serve, bottom pass and top pass). (4) giving rewards. (5) students can perform basic movements well and correctly